Report on verification of Mogfeen 240EC efficacy on Garlic (Allium sativum L) weeds at Bale zone, South Eastern Ethiopia - Guta Eshetu; Mohammedamin Abdulrezak (Open Journal of Plant Science - Peertechz Publications, 2020)
Garlic Herbicide verification trial was conducted at Goba and Sinana districts of Bale highlands south eastern Ethiopia. CBD was used for this experiment. Mogfeen 240EC herbicide was verified by SARC at on station and Goba in 2018 Gena season. The effects of herbicide on the growth, yield components and Yield of Garlic had determined. On the other hand, parameters such as relative weed density (RWD), Weed Index (WI) and Weed Control Index (WCI) were collected to determine the efficacy of Mogfeen 240EC on broadleaf weeds, Sedges and Grass weeds. Accordingly, 99% of Broad leaf weeds and 1% grass weeds were observed before herbicide application. Mogfeen 240EC reduces broad leaves weed by about 82.73% and grass weeds by about 63.022% within first round application. On the other hand, the efficiency of this herbicide in controlling broad leaves weeds within the first round application round was about 73.17% whereas its efficiency in controlling grass weeds was 93.22%. Within the second round application 15 days later of first round application all weeds were controlled completely. On the other hand, plots treated with the herbicide showed about 68.42%, 7.02% yield advantage over weed free and hand weeded plots respectively. Therefore, Mogfeen 240EC herbicide was verified and recommended for the production of Garlic at Bale and similar agro ecologies.